Relasi Agama Dan Budaya Bangsa Dalam Gagasan Abdurahman Wahid Tentang Pribumisasi Islam - Islami, Faza; Ibrohim, Busthomi; Islami, Azmi (Universitas Cokroaminoto Yogyakarta, 2023)
The purpose of this study relates to the identification of Islamic relations and national culture from Abdurrahman Wahid, a national figure who has extraordinary education and experience in the plurality of the Indonesian nation, to then analyze democracy as an important way of religion along with Indonesia's plural culture in the perspective of Maqashid Syariah. A qualitative descriptive character study relies on a basic literature review of Abdurrahman Wahid's various works, including relevant secondary sources. Everything is analyzed for its content so that it can be concluded that Islamization is a model that is not needed in the relations of Islam and national culture in Indonesia. Appreciation for the diversity of the nation is a safe gate so that the religion of Islam becomes a staple color in the nation's culture. This would not have been possible unless they put forward a just democratic life in their society. Options that do not deviate from maqashid Sharia